Metabolic Conservation and Diversification of Metarhizium Species Correlate with Fungal Host-Specificity - Xu, Yong-Jiang; Luo, Feifei; Li, Bing; Shang, Yanfang; Wang, Chengshu (Frontiers in Microbiology, 2016)
The ascomycete genus Metarhizium contains several species of insect pathogenic fungi ranging from specialists with narrow host ranges to generalists that can infect diverse invertebrates. Genetic and metabolic conservations and diversifications of Metarhizium species are not well understood. In this study, using the genome information of seven Metarhizium species, we performed a comparative analysis of gene clusters involved in secondary metabolisms (SMs) in these species. The results revealed that the generalist species contain more SM gene clusters than the specialists, and that both conserved and divergent evolutions may have occurred in SM genes during fungal speciation. In particular, the loss/gain events, as well as gene mutagenesis, are evident for the gene cluster responsible for the biosynthesis of non-ribosomal cyclopeptide destruxins. The presence of conserved SM gene clusters in Metarhizium and other divergently evolved insect pathogenic fungi implies their link to fungal entomopathogenicity. Mass spectrometry based metabolomic analyses were also conducted to investigate the chemical diversities of seven Metarhizium species. Consistent with the evolutionary relationships of SM genes among the seven species, significant differences are observed in fungal metabolic profiles, whether the same or different metabolites are produced in different species. Clustering analysis based on the metabolome data revealed that Metarhizium species could be grouped based on their association to fungal host specificity. Our metabolomics-based methods also facilitate the identification of bioactive metabolites that have not been reported previously in Metarhizium. The results of this study will benefit future investigations of the chemical biology of insect-fungal interactions.